A review of the frequency and impact of periodontal disease in dogs. (21st September 2020) - Wallis, C.; Holcombe, L. J.
Abstract : Periodontal disease is a frequent problem seen in veterinary practices. Primary‐care veterinary practices, where diagnosis of periodontal disease is predominantly based on visual oral assessment of conscious dogs, report an average prevalence of 9.3 to 18.2% within the dog population. Detailed examinations of anaesthetised dogs report much higher prevalence of between 44 and 100%. The prevalence and severity of periodontitis varies between sizes of dogs, breeds and individuals. The lack of robust evaluation of these variances opens the opportunity for a review of the topic. A literature search was therefore undertaken to determine the frequency and extent (severity and oral location) of periodontal disease in the dog population. Both clinical and retrospective data based surveys of veterinary records, show there is an increased likelihood of developing periodontitis as age increases and with bodyweight decreases. The maxillary and mandibular incisors, fourth premolars and first molars are likely to develop the disease first although in some breeds the canines may also be involved. Poor oral care is a significant risk factor for the development of periodontal disease although diet, behaviour, environment and genetics are also likely to play a role. The information provided in this review can be used by veterinarians to improve the effectiveness of their diagnosis, treatments and interventions by focussing their efforts on the sizes, breeds and individuals most at risk. Given the potential link between periodontal disease and systemic health, veterinarians have the opportunity to positively impact the quality of life of a large number of dogs and therefore their owners.